A Case of Basal Cell Carcinoma with Outer Hair Follicle Sheath Differentiation - Masazumi Onishi; Kazuhiro Takahashi; Fumihiko Maeda; Toshihide Akasaka (Karger Publishers, 2015)
A 70-year-old Japanese man presented at our hospital with an asymptomatic, blackish, irregularly shaped plaque with a gray nodule in the periphery on his left lower leg. The lesion had been present for 10 years and had recently enlarged, associated with bleeding. Histopathologically, the tumor consisted of three distinct parts: The first part showed massive aggregation of basophilic basaloid cells with peripheral palisading and abundant melanin granules, and was diagnosed as solid-type basal cell carcinoma. The second part showed aggregation of clear cells with squamous eddies, and was diagnosed as proliferating trichilemmal tumor. The third part showed reticular aggregation of basaloid cells with infundibular cysts in the papillary dermis, and was diagnosed as infundibulocystic basal cell carcinoma. We diagnosed this tumor as basal cell carcinoma with various forms of hair follicle differentiation, including differentiation into the outer root sheath.